Comparative analysis of different numerical schemes in solute trapping simulations by using the phase-field model with finite interface dissipation - Yang X.; Tang Y.; Cai D.; Zhang L.; Du Y.; Zhou S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Two different numerical schemes, the standard explicit scheme and the time-elimination relaxation one, in the framework of phase-field model with finite interface dissipation were employed to investigate the solute trapping effect in a Si-4.5 at.% As alloy during rapid solidification. With the equivalent input, a unique solute distribution under the steady state can be obtained by using the two schemes without restriction to numerical length scale and interface velocity. By adjusting interface width and interface permeability, the experimental solute segregation coefficients can be well reproduced. The comparative analysis of advantages and disadvantages in the two numerical schemes indicates that the time-elimination relaxation scheme is preferable in one-dimensional phase-field simulation, while the standard explicit scheme seems to be the only choice for two- or three dimensional phase-field simulation. Furthermore, the kinetic phase diagrams in the Si-As system were predicted by using the phase-field simulation with the time-elimination relaxation scheme.